Archives and Technological Selection - Lundemo, Trond (Cinémas, 2014)
The archive is not a place for the undifferentiated storage of the past: the political role of the archive is to select what to include as the past and what to discard, in order to regulate the future. These selections are prescribed by laws and regulations, but they are also determined by the archival techniques available for inscription, storage, indexing and access. The author analyses the technological selections of two ages of the archive. The first age is that of the intermedial archive emerging after the end of the text archive monopoly, with the gramophone, photograph and, in particular, film. The gaps and contradictions resulting from this configuration of media are investigated through a discussion of the media set-up of Albert Kahn’s Les archives de la planète (1908-1931). The second age is that of the digital archives, and the digitization of analogue material, again with Les archives de la planète as an example. Instead of understanding these ages of archival technologies as autonomous and separate, the author argues that they should be approached as “superimposed” archival regimes in order to tease out the current interrelations between analogue and digital archives.